Body Image Dissatisfaction In Body Shaming Victims - Lestari, Hanafiani; Saut H. Hutahaean, Erik; Fahrudin, Adi (Jurnal KESANS : Kesehatan dan Sains, 2023)
Introduction: The existence of body shaming indicates a lack of acceptance of the appearance of different body shapes. This problem is especially prevalent among teenagers, who often ridicule their peers. Body shaming has serious consequences, including body image dissatisfaction, eating disorders and depression. Objective: to examine body image dissatisfaction in adolescents who have been subjected to body shaming. A total of 120 participants were involved in this study, and they were selected based on their willingness to complete the body image dissatisfaction scale questionnaire. Methods: This study used a quantitative approach and used correlation to analyze the body image dissatisfaction scale, the Multidimensional Body-Self Relations Questionnaire-Apperance Scales (MBSRQ-AS). Results and discussion: the study showed that individuals who experienced body image dissatisfaction due to body shaming also experienced decreased self-esteem. Conclusion: body shaming can significantly contribute to body image dissatisfaction and low self-esteem.